2017
DOI: 10.3389/fpls.2017.00434
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Maize Dof1 Transcription Factor in Wheat and Sorghum

Abstract: Nitrogen is essential for plant growth and development. Improving the ability of plants to acquire and assimilate nitrogen more efficiently is a key agronomic parameter that will augment sustainability in agriculture. A transcription factor approach was pursued to address improvement of nitrogen use efficiency in two major commodity crops. To this end, the Zea mays Dof1 (ZmDof1) transcription factor was expressed in both wheat (Triticum aestivum) and sorghum (Sorghum bicolor) either constitutively, UBI4 promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…Many plants display a relatively low NUE because they are ineffective at accessing soil N and may take up as little as 41% of supplied N fertilizer (Hodge et al, 2000;Kumar and Goh, 2002;Thornton and Robinson, 2005;Yang et al, 2015;Zhu et al, 2016). Research on improving NUE has focused on the manipulation of nitrate and ammonium transporters (Fraisier et al, 2000;Yuan et al, 2007;Tsay et al, 2011;Fang et al, 2013;Ranathunge et al, 2014;Bao et al, 2015;Chen et al, 2016Chen et al, , 2017Fan et al, 2016;Wang et al, 2018aWang et al, , 2018b, associated transcription factors (Qu et al, 2015;Araus et al, 2016), or the ectopic expression of genes involved in amino acid synthesis and N metabolism (Ameziane et al, 2000;Chichkova et al, 2001;Habash et al, 2001;Yamaya et al, 2002;Seiffert et al, 2004;Good et al, 2007;Shrawat et al, 2008;McAllister et al, 2012;Peña et al, 2017). Although promising results have been achieved with respect to seed yields and NUE, these studies rarely analyzed both NUE-contributing factors, NUpE and NUtE, or the effects of different N environments (Kiba and Krapp, 2016;Tegeder and Masclaux-Daubresse, 2018).…”
Section: Leaf Amino Acid Supply Affects Photosynthetic and Plant Nitrmentioning
confidence: 99%
“…Many plants display a relatively low NUE because they are ineffective at accessing soil N and may take up as little as 41% of supplied N fertilizer (Hodge et al, 2000;Kumar and Goh, 2002;Thornton and Robinson, 2005;Yang et al, 2015;Zhu et al, 2016). Research on improving NUE has focused on the manipulation of nitrate and ammonium transporters (Fraisier et al, 2000;Yuan et al, 2007;Tsay et al, 2011;Fang et al, 2013;Ranathunge et al, 2014;Bao et al, 2015;Chen et al, 2016Chen et al, , 2017Fan et al, 2016;Wang et al, 2018aWang et al, , 2018b, associated transcription factors (Qu et al, 2015;Araus et al, 2016), or the ectopic expression of genes involved in amino acid synthesis and N metabolism (Ameziane et al, 2000;Chichkova et al, 2001;Habash et al, 2001;Yamaya et al, 2002;Seiffert et al, 2004;Good et al, 2007;Shrawat et al, 2008;McAllister et al, 2012;Peña et al, 2017). Although promising results have been achieved with respect to seed yields and NUE, these studies rarely analyzed both NUE-contributing factors, NUpE and NUtE, or the effects of different N environments (Kiba and Krapp, 2016;Tegeder and Masclaux-Daubresse, 2018).…”
Section: Leaf Amino Acid Supply Affects Photosynthetic and Plant Nitrmentioning
confidence: 99%
“…However, efforts to increase N uptake and NUpE through the manipulation of nitrate and ammonium transporters or associated transcription factors have had only limited success (Fraisier et al, 2000;Yuan et al, 2007;Tsay et al, 2011;Ranathunge et al, 2014;Qu et al, 2015;Araus et al, 2016;Chen et al, 2017). Furthermore, varying outcomes have been reported from the ectopic expression of genes involved in amino acid synthesis and N metabolism (Ameziane et al, 2000;Chichkova et al, 2001;Habash et al, 2001;Yamaya et al, 2002;Seiffert et al, 2004;Good et al, 2007;Shrawat et al, 2008;McAllister et al, 2012;Peña et al, 2017). However, these studies rarely addressed the different components of NUE (i.e.…”
Section: Nue Is Greatly Improved In Aap1-oe Plantsmentioning
confidence: 99%
“…Nitrogen utilization efficiency (NUtE) is defined as total seed yield relative to total shoot N content (Moll et al, 1982) and is affected by several physiological factors, including N uptake, metabolism, allocation, and remobilization (Habash et al, 2001;Tsay et al, 2011;Girondé et al, 2015). In addition, regulated transport of N within the plant strongly influences the amount of N allocated to seeds and final seed yields (Rolletschek et al, 2005;Schmidt et al, 2007;Weigelt et al, 2008;Tan et al, 2010;Zhang et al, 2010Zhang et al, , 2015Carter and Tegeder, 2016;Santiago and Tegeder, 2016 Araus et al, 2016;Chen et al, 2017), nitrate allocation (Tsay et al, 2011), N metabolism (Ameziane et al, 2000Chichkova et al, 2001;Habash et al, 2001;Yamaya et al, 2002;Seiffert et al, 2004;Good et al, 2007;Shrawat et al, 2008;Peña et al, 2017), and its regulation (Yanagisawa et al, 2004). While generally successful, these studies often did not address the different components of NUE (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many genes involved in stress response can be simultaneously regulated by a single gene encoding stress inducible transcription factor (Kasuga et al, 1999). While the expression of ZmDof1 transcription factor in sorghum and wheat has activated the primary target, phosphoenolpyruvate carboxylase (PEPC), which leads to the down-regulation of genes involved in photosynthesis and the functional apparatus of chloroplasts, and negatively impacted photosynthesis, and biomass (Peña et al, 2017). These results indicated that transcription factor strategies for crop improvement need to consider the downstream targets of the genetic elements to be introduced.…”
Section: Discussionmentioning
confidence: 99%